Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Conférence: «Histoire de l'art et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Thérèse St-Gelais, directrice de l'Institut de recherches et d'études féministes et professeure au Département d'histoire de l'art.
Keywords: amériques; approches et analyses; arts; corps; création; discipline; femmes* artistes; histoire de l'art; histoire des femmes*; histoire du féminisme; oeuvre; performance; point de vue situé; postmodernisme; québec; ressource en ligne; régions géographiques; thématiques; violences; émotions

"Why Should Our Bodies End at the Skin?": Embodiment, Boundaries, and Somatechnics - SHILDRICK, MARGRIT (Hypatia, 2015)
Donna Haraway's enduring question—"Why should our bodies end at the skin?" (Haraway 1990, 220)—is ever more relevant in the postmodern era, where issues of bodies, boundaries, and technologies increasingly challenge not only the normative performance of the human subject, but also the very understanding of what counts as human. Critical Disability Studies has taken up the problematic of technology, particularly in relation to the deployment of prostheses by people with disabilities. Yet rehabilitation to normative practice or appearance is no longer the point; instead, the lived experience of disability generates its own specific possibilities that both limit and extend the performativity of the embodied self. I look at what is at stake in the challenge to the Western logos that comes specifically from the capacities of the disabled body, understood not as a less than perfect form of the normative, but as figuring difference in a nonbinary sense. Feminist theory has long contested the isomorphism of the logos, but I go beyond simply setting out the grounds for revaluing multiple variant forms. The feminist turn to Jacques Derrida and Gilles Deleuze opens up the problematic to a celebratory positioning of difference and transcorporeality as the very conditions of life.
Keywords: EDI; approches et analyses; arts; bioéthique; corps; cours; discipline; philosophie; postmodernisme; premier cycle; prothèses; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; technologie; thématiques; études critiques du handicap; études littéraires

Écouter "vraiment" : une méthodologie des sensibilités - Caron, Caroline (Vues, mais non entendues : les adolescentes québécoises et l'hypersexualisation, 2014)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; adolescentes*; amérique du nord; amériques; approches et analyses; canada; communication; corps; discipline; discours dominant; discours médiatique; féminisme postmoderne; hypersexualisation; hétérosexisme; identités LGBTQIA2+; injustices épistémiques; point de vue situé; postmodernisme; périodes historiques; québec; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; école

L'anatomie politique: catégorisations et idéologies du sexe - Mathieu, Nicole-Claude (Racine de iXe, 2013)
Dans toutes les sociétés, et que les acteurs sociaux en soient conscients ou non, la conception du sexe anatomique comporte toujours un aspect stratégique, c'est-à-dire politique, dans l'organisation des relations entre les sexes. Deux questions se posent et se croisent : la conceptualisation du sexe (quel rapport établit-on entre le biologique et le social ?) et la catégorisation des sexes (qu'est-ce qu'un homme, qu'est-ce qu'une femme, qu'est-ce que du masculin, du féminin, de l'unisexe ou du troisième genre... ?). Si l'oppression des femmes est générale, les idéologies du sexe sont diverses. L'auteur s'est intéressée à ceux et celles qui parlent et à celles qui se taisent, aux métamorphoses subtiles du discours savant, aux interprétations et aux déterminants de la conscience des femmes, aux normes des sociétés et des individus sur le sexe et le genre, et aux tentatives de subversion. Que ce soit du côté des normes ou du côté des contestataires, et qu'elles disent que le genre traduit, ou symbolise, ou construit le sexe, les idéologies témoignent du sexe social : que l'anatomie est politique.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sexe; sexe/genre; shm4000; systèmes d'oppressions; thématiques